Effects of Variation of Quantum Well Numbers on Gain Characteristics of Type-I InGaAsP/InP Nano-heterostructure - S. G. Anjum; Sandhya K.; A. B. Khan; A. M. Khan; M. J. Siddiqui; P. A. Alvi (Institute of Advanced Engineering and Science, 2017)
This paper reports the effects of variation of number of quantum wells in material gain characteristics and lasing wavelength of step index separately confined type-I InGaAsP/InP lasing nano-heterostructure for different carrier concentrations at room temperature in TE (Transverse Electric) mode of polarization. Peak material gain is found to be highest when the number of quantum well is one in the structure. However, for the case of 3QWs, 5QWs and 7QWs, it is almost same at a particular carrier density. Lasing wavelength at peak material gain considerably increases as the number of quantum well layers vary from single quantum well layer to three quantum well layers in the active region and after that it will remain almost same by any further increase in number of quantum wells for a particular carrier density. Furthermore, negative gain condition in the material gain spectra exists in the case of multiple quantum wells only at carrier concentration of 2×1018/cm3. The results suggest that the proposed nano-heterostructure is highly suitable as a light source in fiber optic links for long distance communication.